Evaluasi Program Projek Penguatan Profil Pelajar Pancasila Multi Situs SMA di Kabupaten Gresik - Shelvie Sari Sukma; Ayu Wulandari; Nunuk Hariyati; Amrozi Khamidi; Mochamad Nursalim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) program in schools, by highlighting the supporting and inhibiting factors in its implementation. Using a qualitative research method with a descriptive approach, data were collected through interviews, observations, and documentation from various related parties, such as principals, teachers, and students. The results of the study indicate that in terms of context, program planning in several schools was carried out collaboratively with the local community, although there were obstacles in the understanding of school staff regarding the essence of P5. In terms of input, teacher readiness varies, with some teachers still requiring additional training in implementing P5. Facilities and budget allocation are also challenges in supporting optimal program implementation. In terms of process, the implementation of P5 involves various activities based on Pancasila values, although variations in methods and limited facilities in several schools affect its effectiveness. Monitoring and evaluation of the program still require a more structured system to measure the achievement of program objectives on an ongoing basis. In terms of product, P5 has been shown to improve students' understanding of Pancasila values, 4C skills (Communication, Collaboration, Critical Thinking, Creativity), and produce various project-based learning products. However, challenges in the consistency of the application of Pancasila values ​​and limited resources are still obstacles in the implementation of this program. Therefore, more equitable teacher training, increased community support, and innovation in teaching methods are needed to ensure the success of the P5 program in various schools. Keywords: Pancasila Student Profile Strengthening Project, Implementation, Program Evaluation, Character Education